Gut microbiome-mediated mechanisms for reducing cholesterol levels: implications for ameliorating cardiovascular disease - Jia, Baolei; Zou, Yuanqiang; Han, Xiao; Bae, Jin-Woo; Jeon, Che Ok (Trends in microbiology (Regular ed.), 2023)
Cardiovascular disease (CVD) is a health problem worldwide, and elevated cholesterol levels are a key risk factor for the disease. Dysbiotic gut microbiota has been shown to be associated with CVD development. However, the beneficial effects of healthy microbiota in decreasing cholesterol levels have not been summarized. Herein, we begin by discussing the potential mechanisms by which the gut microbiota reduces cholesterol levels. We further sketch the application of probiotics from the genera Lactobacillus and Bifidobacterium in reducing cholesterol levels in clinical studies. Finally, we present the cholesterol-lowering function of beneficial commensal microbes, such as Akkermansia and Bacteroides spp., as these microbes have potential to be the next-generation probiotics (NGPs). The information reviewed in this paper will help people to understand how the gut microbiome might alter cholesterol metabolism and enable the development of NGPs to prevent and treat CVD. Short-chain fatty acids and secondary bile acids can decrease cholesterol levels by regulating cholesterol metabolism.Microbial bile salt hydrolases can increase cholesterol disposal rates by accelerating its conversion to bile acids.Uncultured bacteria from the human gut can transform cholesterol to coprostanol.Probiotics from the genera Lactobacillus and Bifidobacterium are efficient reducers of cholesterol levels in clinical studies.Several candidate next-generation probiotics, including Akkermansia muciniphila, Bacteroides spp., Clostridium spp., Christensenella minuta, Eubacterium spp., and Faecalibacterium prausnitzii, have been shown to decrease cholesterol levels in human or animal studies.